The value of forecasting BYDV in autumn sown cereals - Bicknell, K.; Greer, G.; Teulon, D.A.J. (New Zealand Plant Protection, 2000)
Crop Food Research has developed a model to forecast the occurrence of severe barley yellow dwarf virus (BYDV) incidence in autumnsown wheat crops in Canterbury based on alate aphid flights This information is potentially valuable to growers in Canterbury who can modify their inputs each year according to the risk of BYDV This paper uses expected gross margins to estimate the financial benefit of the Crop Food Research BYDV Forecast Service to arable growers in Canterbury Results suggest that the value of the BYDV Forecast Service is positive but varies greatly depending upon forecast accuracy and adoption rate